Compressive Strength Performance of Rice Husk Ash-Based Geopolymer Concrete with Fly Ash as a Secondary Material - Olii, Muhammad Ramdhan; Saliko, Maxidin; Doda, Nurhayati; Nento, Sartan; Olii, Rizky Selly Nazarina (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Concrete production heavily relies on cement, whose manufacturing significantly contributes to carbon emissions, necessitating alternative materials for sustainable construction. This study investigates the effect of varying compositions of rice husk ash (RHA) and fly ash on the compressive strength and workability of concrete. Five variations of RHA and fly ash ratios (80:20, 75:25, 70:30, 65:35, and 60:40) were tested to identify the optimal mixture. The results show that the 60:40 ratio produced the highest compressive strength of 16.66 MPa and a slump value of 9.5 cm, indicating enhanced workability and mechanical performance. This finding highlights the complementary roles of RHA, which contributes to pozzolanic activity, and fly ash, which enhances hydration and cementitious properties. Excessive RHA content, however, leads to reduced strength due to its lower reactivity. The exponential trend observed in the compressive strength characteristics (R² = 0.9081) confirms the nonlinear relationship between material composition and performance. This research aligns with previous studies demonstrating the benefits of using industrial by-products in concrete. The findings underscore the potential of combining RHA and fly ash as an eco-friendly solution for high-strength concrete, promoting waste utilization and sustainability in the construction industry. Future studies should explore long-term durability and scaling for industrial applications.